A preliminary study on l-lysine fermentation from lignocellulose feedstock and techno-economic evaluation. (January 2019) - Chen, Zeyu; Liu, Gang; Zhang, Jian; Bao, Jie
Graphical abstract: Highlights: 33.8 g/Ll -lysine was obtained using corn stover after a dry biorefining process. The minimum cellulosicl -lysine selling price was calculated to be 2.445 per kg. It has a great potential to producel -lysine using lignocellulose feedstock. Abstract: l -Lysine is a commodity amino acid produced from starch feedstock. Various alternative feedstocks had been used forl -lysine production, but the yield was very low. This study took the first preliminary investigation onl -lysine production from lignocellulose for the replacement of food-crop starch. Corn stover was dry acid pretreated and biodetoxified, then used for enzymatic hydrolysis andl -lysine fermentation by an industrial Corynebacterium glutamicum strain. Various fermentation parameters, nutrient additions, and operation variables were applied and finally 33.8 g/L ofl -lysine was obtained. Thisl -lysine titer is still below that of starch based fermentation, but already 3–5 folds greater than that of other alternative feedstocks based fermentation. A techno-economic analysis was conducted and the minimum selling price ofl -lysine (hydrochloride form) was calculated to be 2.445 per kg. The cost reduction by the future improvement could fill the technical and economic gap between the cellulosic and starch basedl -lysine production.